2015
DOI: 10.1080/07391102.2015.1052849
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies on the buffalo prion protein

Abstract: It was reported that buffalo is a low susceptibility species resisting to transmissible spongiform encephalopathies (TSEs) (same as rabbits, horses, and dogs). TSEs, also called prion diseases, are invariably fatal and highly infectious neurodegenerative diseases that affect a wide variety of species (except for rabbits, dogs, horses, and buffalo), manifesting as scrapie in sheep and goats; bovine spongiform encephalopathy (BSE or "mad-cow" disease) in cattle; chronic wasting disease in deer and elk; and Creut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The above bioinformatics might be acted as a "quick reference card" for PrP protein structure π-interaction studies [1,2].…”
mentioning
confidence: 99%
“…The above bioinformatics might be acted as a "quick reference card" for PrP protein structure π-interaction studies [1,2].…”
mentioning
confidence: 99%
“…A comparative study revealed that the SPRN gene has species-speciic indel polymorphisms in catle and bufaloes and causes diferent promoter activity and expression levels [144]. Furthermore, according to the results of more recent study, molecular structure of bufalo cellular prion protein is diferent from catle, but similar to those of rabbits, dog and horse which are considered low susceptible to TSEs [145]. These molecular and structural diferences may be another explanation with regard to TSEs resistance in bufaloes.…”
Section: Prion -An Overviewmentioning
confidence: 86%
“…Mammals carrying a flexible β2–α2 loop are easily infected by prions, while in animals carrying a rigid loop, prions are poorly infected [51]. Notably, the horse, rabbit, dog, and buffalo are mammalian species reported as resistant to infection from prion diseases isolated from other species [52,53,54,55].…”
Section: The Structure Of the N-terminal And C-terminal Domainsmentioning
confidence: 99%
“…The flexibility in the variation facilitates the access to alternate conformational states of the protein, remodeling the sites for molecular recognition events (i.e., protein-protein and protein-ligand interactions) [57]. Molecular dynamics studies have revealed that in rabbits, dogs, horses, and buffalo [52,53,54,55], species resistant to infection from prion diseases, there is a strong salt bridge Asp178-Arg164 (O-N) keeping the β2–α2 loop closely linked and contributing to the structural stability of prion protein. Another recent study about the low prion susceptibility of canids, based on the amino acid sequence of the canine PrP, identified the relevance of the Asp163 amino acid in proneness to protein misfolding, showing it was a key amino acid with characteristics responsible for the high resistance to prion disease [58].…”
Section: The Structure Of the N-terminal And C-terminal Domainsmentioning
confidence: 99%